Temperament and attachment as predictive factors for the risk of addiction to substances in adolescents. - Cornellà-Font, Maria G.; Viñas-Poch, Ferran; Juárez-López, Josep R.; Martín-Perpiñá, Maria de las M.; Malo-Cerrato, Sara (Revista de Psicopatología y Psicología Clínica, 2019)
Abstract: This study aims to relate the dimensions of temperament and attachment with the risk of addiction to substances in a group of 642 adolescents between 13 and 19 years old, and to assess which dimensions of these constructs acted as risk or protective factors. It also relates the two constructs between them. There was a positive correlation between the risk of addiction and the temperament dimension "Novelty seeking" and with those of attachment, "Self-sufficiency and parental resentment" and "Child trauma". The correlation was negative with "Persistence" (temperament) and "Security" (attachment). "Novelty seeking", "Family concern" and age, acted as risk factors; whereas “Security” in attachment was a factor of protection. The temperament and attachment profiles with a higher risk of addiction correlated with each other; they also correlated those with a low risk. Resumen: Temperamento y apego como factores predictivos para el riesgo de adicción a sustancias en adolescentes.Este estudio busca relacionar las dimensiones de temperamento y apego con el riesgo de adicción a sustancias en un grupo de 642 adolescentes de entre 13 y 19 años, y valorar qué dimensiones de estos constructos actúan como factores de riesgo o de protección. También se relacionan los dos constructos entre ellos. Hubo una correlación positiva entre el riesgo de adicción y la dimensión de temperamento “Búsqueda de novedad”, y con las de apego “Autosuficiencia y rencor hacia los padres” y “Trauma infantil”. La correlación fue negativa con “Persistencia” (temperamento) y “Seguridad” (apego). “Búsqueda de la novedad”, “Preocupación familiar” y edad, actuaron como factores de riesgo; mientras que la “Seguridad “en el apego fue un factor de protección. Los perfiles de temperamento y apego con riesgo más elevado de adicción correlacionaron entre ellos; también correlacionaron aquellos con un riesgo bajo.